(untitled) (Development Service Industry Management, 2023)
The purpose of the article is to identify challenges and development scenarios for the domestic automotive industry, taking into account its current state. The importance of the automotive industry as a sector in various countries around the world is highlighted, making a significant contribution to GDP, contributing to export revenue, being a major employer, and stimulating demand in related industries. It is shown that in many countries, state support is provided for the development of the automotive industry. A research logic is developed based on identifying specific stages of research and proposing research methods for each of these stages. The research stages include defining current trends in the automotive industry in Ukraine and identifying challenges and development scenarios for the Ukrainian automotive industry. Identified phenomena in the Ukrainian automotive industry include the contraction of domestic production, the shift from producing finished products to assembly and manufacturing individual components, significant regional disparities in operating conditions, high logistic dependence on external agents, lack of state support for the industry, insufficient domestic demand, and the growth of the electric vehicle segment. Challenges for the automotive industry in Ukraine have been defined. It is emphasized that these identified challenges are pertinent to the industry as a whole and cannot be overcome solely at the level of an individual manufacturer. These challenges include restricted access to certain raw materials, a shortage of qualified personnel, high energy intensity of domestic production, non-competitiveness of finished products in foreign markets, low purchasing power in the domestic market, energy supply disruptions, the possibility of property loss due to armed conflict, the development of the electric vehicle segment, logistic issues, a lack of funds for financing activities and development. For each identified challenge, its essence and the reasons for its occurrence are disclosed. Scenario analysis has allowed the identification of potential future development scenarios for the domestic automotive industry in Ukraine, including further stagnation and degradation of the industry, growth of specialized production through state orders, formation of product and/or geographical clusters, integration into global value chains, technological breakthrough, integration into the electric vehicle segment, elemental specialization, and service orientation. For each of these scenarios, their essence and factors of actualization are disclosed.